Screening and Characterization of Lactic Acid Bacteria Producing Antimicrobial Substance against Staphylococcus aureus - Chatinan Ratanapibulsawat; Pumrussiri Kroujkaew; Ohmomo Sadahiro; Sunee Nitisinprasert (Agriculture and Natural Resources, 2005)
One isolate of lactic acid bacteria (LAB) producing antimicrobial substance (AMS) against Staphylococcus aureus was selected and designed as LS2-30. Morphological, physical and biochemical tests, and 16S rRNA analysis were performed and revealed that it was Pediococcus acidilactici. Optimal conditions for growth and AMS production were determined. The optimum temperature and initial pH for both growth and AMS production were 45 oC and pH 6, respectively. Cell-free culture fluid of LS2-30 showed an inhibitory action against Staphylococcus aureus, Salmonella sp., Bacillus sp., and E. coli but no activity against all LAB tested. When mode of action was studied, the cell-free culture fluid exhibited a bactericidal mode of action but did not lyse its cells. After removing organic acids, partial purified antimicrobial substance at pH 3 showed inhibitory activity as bactericidal action. Hydrolytic enzyme treatment suggested that AMS structure was neither proteinaceous, starch nor lipid moiety in nature. Therefore, the nature of inhibitory compound secreted by P. acidilactici LS2-30 was still unclear.